ANALISIS PERLAKUAN AKUNTANSI ASET TETAP PADA DINAS PEKERJAAN UMUM (PU) PROVINSI SULAWESI UTARA - Tipan, Akhyar; Saerang, David Paul Elia; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Fixed assets have a very important role for the smooth operation of government services to maximize the activity takes appropriate policy in the management of fixed assets. Department of Public Works (PU) North Sulawesi is an institution that supports the affairs of the District / Town in the field of public works who carry out tasks in the District / City of North Sulawesi. Service vehicles, equipment and machinery, land, buildings, roads, and the fixed assets owned by the Department of Public Works North Sulawesi and very important in supporting the activities of government services. This study aimed to analyze the accounting treatment for fixed assets at the Department of Public Works North Sulawesi what was in accordance with Regulation 71 Year 2010 Statement of Government Accounting Standards (PSAP) No. 07 of the fixed assets. The method used is descriptive analysis method with a way to understand the reality and compare it with the theory that the researchers studied so it can be concluded. In the study the accounting treatment of fixed assets has been good. In practice, in the way of acquisition of fixed assets Public Works Department to make a purchase in cash, Department of Public Works has not shrunk its fixed assets where it is not in accordance with the Governmental Accounting Standards applicable, Department of Public Works to stop the fixed assets that are not used by way of eliminating it from the balance sheet and transferred to the post other fixed assets, as well as in the presentation and disclosure, the Department of Public Works has revealed the fixed assets in accordance with accounting standards applicable rule.